Performance of 8 Smoking Metrics for Modeling Survival in Head and Neck Squamous Cell Carcinoma - Lam, Andrew C L; Hueniken, Katrina; Pienkowski, Martha; Lee, John J W; Dong, Mei; Diergaarde, Brenda; Olshan, Andrew F; Brennan, Paul; Virani, Shama; Saunders, Deborah; Santi, Stacey A; Conlon, Michael S C; et al. (JAMA otolaryngology - head & neck surgery, 2025)
IMPORTANCE: Cigarette smoking is a strong risk factor for mortality in patients diagnosed with head and neck squamous cell carcinoma (HNSCC). However, little evidence supports which smoking metric best models the association between smoking and survival in HNSCC. OBJECTIVE: To determine which smoking metric best models a linear association between smoking exposure and overall survival (OS) in patients with HNSCC. DESIGN, SETTING, AND PARTICIPANTS: A retrospective multicenter cohort study of 6 clinical epidemiological studies was performed. Five were part of the Human Papillomavirus, Oral and Oropharyngeal Cancer Genomic Research (VOYAGER) consortium. Participants included patients 18 years and older with pathologically confirmed HNSCC. Data were collected from January 2002 to December 2019, and data were analyzed between January 2022 to November 2024. MAIN OUTCOMES AND MEASURES: The primary outcome was OS. The performance of 8 smoking metrics, including pack-years, duration, and log cig-years (calculated as log10[cigarettes smoked per day + 1] × number of years smoked) for modeling OS were compared. Metric performance was measured by the strength of association in Cox proportional hazard models, linearity based on P for linear trend, Akaike information criterion (AIC; lower value indicates better model fit), and visual assessment of spline curves. Secondary outcomes included modeling OS in clinicodemographic subgroups and HNSCC anatomic subsites. Exploratory outcomes included cancer-specific survival and noncancer survival. RESULTS: In total, 8875 patients with HNSCC (2114 [24%] female; median [IQR] age, 61 [54-69] years) were included. Of 8 smoking metrics evaluated, smoking duration (adjusted hazard ratio [aHR], 1.11 [95% CI, 1.03-1.19]) and log cig-years (aHR, 1.11 [95% CI, 1.04-1.18]) had the highest aHRs; both had a statistically significant linear association with OS. Log cig-years had the lowest AIC linear value and the most visually linear spline curve when modeling OS. Duration and log cig-years outperformed pack-years for modeling OS regardless of age, smoking status, and cancer stage. Both performed well in lip and oral cavity, laryngeal (only duration was significant), and human papillomavirus-negative oropharyngeal subsites. In an exploratory analysis, duration had the highest aHR (1.15 [95% CI, 1.02-1.29]), and log cig-years had the lowest AIC linear value when modeling noncancer survival. CONCLUSIONS AND RELEVANCE: In this cohort study, smoking duration and log cig-years best modeled a linear relationship with OS for patients with HNSCC. Both metrics maintained robust performance within specific clinicodemographic subgroups and anatomic subsites. Although most HNSCC survival models control for smoking exposure using smoking status or pack-years, duration and log cig-years may be superior metrics to account for the effects of smoking on survival.
Keywords: proporcionální rizikové modely; Squamous Cell Carcinoma of Head and Neck; Male; retrospektivní studie; dlaždicobuněčné karcinomy hlavy a krku; Risk Factors; Survival Rate; Proportional Hazards Models; nádory hlavy a krku; Aged; Head and Neck Neoplasms; mužské pohlaví; senioři; kouření cigaret; Smoking; Cigarette Smoking; lidé; ženské pohlaví; Humans; rizikové faktory; Retrospective Studies; Female; lidé středního věku; kouření; míra přežití; Middle Aged